The life of John Milton : with conjectures on the origin of Paradise lost / by William Hailey, Esq. - Hayley, William, 1745-1820. (Tufts University. Tisch Library., 2016)
1 online resource ([4], xxiv, 362 pages); With a half-title.; "Appendix, containing extracts from the Adamo of Andreini: with an analysis of another Italian drama, on the same subject": pages [317]-362.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.